“Hygiene in construction site” / Nursuhana Chat - Chat, Nursuhana (2006)
Malaysia is an international city with a beautiful harbour and prestigious high rise buildings. Are our buildings looking nice? We have risk of dengue fever that affects our daily life economic. Workers housekeeping at construction site is considered the fundamental key for all the issues. We need enhance it.